Design of Fully Differential Operational Amplifier with High Gain, Large Bandwidth and Large Dynamic Range - Kumar, Manish (My University, 2009)
This thesis work presents the full custom design of a two-stage fully differential CMOS amplifier with outstanding characteristics of high unity-gain bandwidth and large dynamic range at output. The circuit has been designed. The simulation results in TSMC 0.35μm CMOS process from a 3.3V voltage-supply demonstrate that the designed operational amplifier has satisfied state-of-the-art design specifications with a dedicated optimization technique. This fully differential op-amp can be used in a pipeline ADC stage. The amplifier consists of four parts, a telescopic differential amplifier that provides most of the open loop gain, second stage common source amplifier that provide the output swing, a common mode feedback circuit to maintain the constant output voltage and a compensation circuitry for achieving desired phase margin with high unity gain bandwidth. The amplifier exhibit large output swing of 3.1 V peak-to-peak, a fast settling time 2.8 ns to the accuracy of 1%. While the open loop amplifier have the considerable gain as high as 86.02 dB, the differential AC loop unity gain bandwidth reaches 270 MHz and the dynamic range at the output gets 85.15dB with phase margin of 50°. The present work also demonstrate how to efficiently design and further optimize the circuit topology and parameters in order to meet some strict specifications given in advance for a specific engineering project.
Master of Technology (VLSI Design & CAD)
Keywords: Fully Differentail; operational amplifier